2016
DOI: 10.1248/bpb.b16-00414
|View full text |Cite
|
Sign up to set email alerts
|

Isorhamnetin Inhibits Reactive Oxygen Species-Dependent Hypoxia Inducible Factor (HIF)-1α Accumulation

Abstract: Isorhamnetin is a flavonoid metabolite of quercetin and isolated from water dropwort (Oenanthe javanica, Umbelliferae). It has been reported that isorhamnetin exerts beneficial effects including antioxidant, anti-inflammatory, and anti-proliferative activities. The present study investigated whether the antioxidant activity of isorhamnetin is correlated with its anti-cancer effects on colorectal cancer cells. Key words colorectal cancer; hypoxia-inducible factor-1α; isorhamnetin; reactive oxygen species Isorha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…The beneficial effects of isorhamnetin, such as anti-inflammatory, antioxidant and anti-cancer have been reported in various tissues [ 36 , 37 , 38 ]. Seo et al [ 39 ] determined that the antioxidant activity of isorhamnetin was correlated with its anti-cancer effects on colorectal cancer cells. The results demonstrated that isorhamnetin inhibits reactive oxygen species (ROS)-mediated hypoxia-induced hypoxia inducible factor-1α (HIF-1α) accumulation, which contributes to its anti-metastatic efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…The beneficial effects of isorhamnetin, such as anti-inflammatory, antioxidant and anti-cancer have been reported in various tissues [ 36 , 37 , 38 ]. Seo et al [ 39 ] determined that the antioxidant activity of isorhamnetin was correlated with its anti-cancer effects on colorectal cancer cells. The results demonstrated that isorhamnetin inhibits reactive oxygen species (ROS)-mediated hypoxia-induced hypoxia inducible factor-1α (HIF-1α) accumulation, which contributes to its anti-metastatic efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…This compound is one of the metabolites of quercetin that is structurally similar to kaempferol, also known as 3'-O-methyl quercetin (Castrillo et al 1986;Rösch et al 2004;Chen et al 2013). Isorhamnetin exhibits many biological properties due to its anti-inflammatory, antioxidant and metabolic properties (Luo et al 2015;Seo et al 2016;Yang et al 2016;Abdallah and Esmat 2017;Qi et al 2018), and is also considered to have the potential of anti-cancer agents in the results of various cancer cell models. According to previous studies, isorhamnetin has been reported to prevent the proliferation of human leukemia, breast cancer, colon cancer and cervical cancer cells through G2/M phase arrest (Li et al 2014;Wu et al 2016;Wei et al 2018;Zhang et al 2018), and to induce mitotic block in non-small cell lung carcinoma cells, thus enhancing cisplatin-and carboplatin-induced G2/M arrest (Zhang et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…18 Therefore, we used the CoCl 2 to create a hypoxic culture condition and revealed the ability of inhibition of HIF-1α 18 Therefore, we used the CoCl 2 to create a hypoxic culture condition and revealed the ability of inhibition of HIF-1α…”
Section: Inhibition Of Hif-1α and Vegf Expression By Mir-148a In Thmentioning
confidence: 99%
“…From the previous study demonstrated by Seo et al, CoCl 2 is a hypoxia mimetic agent. 18 Therefore, we used the CoCl 2 to create a hypoxic culture condition and revealed the ability of inhibition of HIF-1α and VEGF expression by miR-148a under the hypoxic culture medium. and Friday.…”
Section: Inhibition Of Hif-1α and Vegf Expression By Mir-148a In Thmentioning
confidence: 99%